Load Frequency Control of Single-Area Power System with PI-PD Controller Design for Performance Improvement - Guler, Yavuz; Kaya, Ibrahim (Springer Singapore Pte Ltd, 2023)
Load frequency control (LFC) is an important control problem as it determines the quality of power generation by controlling the system frequency and inter-area tie-line power. To maintain a good quality power supply, LFC must be robust against unknown external disturbances and parameter variations of the power system. Therefore, this paper presents the design of PI-PD controllers, which are robust against parameter changes and have good disturbance suppression capability, for load frequency control of a single-area single- or multi-source power system. PI-PD controller parameters were obtained by applying the weighted geometric center method to the stability boundary locus of the closed-loop control system. The approach was applied to both the inner and outer loops of the PI-PD control system structure, sequentially. Performance and robustness of the proposed PI-PD control system are evaluated using some well-known integral error criteria values, settling time, and peak value (overshoot) in the analysis of the power system with both nominal values and & PLUSMN; 50% changes in the system parameters. The simulation results show that the designed PI-PD controller effectively limits the effect of load disturbance and variations in system parameters.
Keywords: Load Frequency Control; Pi-Pd; Stability Boundary Locus; Wgc Method; Automatic-Generation Control; Stabilizing Pi; Strategy; Computation; Hybrid; Agc